Determination of Aflatoxin M1 and Ochratoxin A in Raw, Pasteurized and UHT Milk in Turkey - Turkoglu, Cagla; Keyvan, Erhan (Acta Scientiae Veterinariae, 2019)
Background: Mycotoxins produced by yeast and fungi have toxic effects on human and animal health. Aflatoxin B1 (AFB1) is the most toxic hepatocarcinogen to mammals. Aflatoxin M1 (AFM1), which has been found in milk and dairy products, is the hydroxylated metabolite of AFB1. Aflatoxin M1 is formed by the cytochrome P450 enzyme in the liver. Ochratoxin A (OTA) is synthesized by Aspergillus and Penicillium species. Ochratoxin A is known to cause teratogenic, immunotoxic, nephrotoxic and carcinogenic effects. Due to the potential harmful effects on human and animal health, OTA has also been receiving increased attention globally; however, there is limited information on the presence of OTA in milk and dairy products. The aim of this study was to determine how mycotoxins impact the hygienic quality of raw and heat-processed milk. Materials, Methods & Results: In this study, a total of 105 milk samples were analyzed (35 raw, 35 pasteurized and 35 UHT) to identify AFM1 and OTA in raw, pasteurized and ultra-high temperature processing (UHT) milk. The levels of AFM1 were detected by using the enzyme-linked immunosorbent assay (ELISA). The milk samples were centrifugedin order to remove the fat content from the milk. After centrifugation, the upper cream layer was withdrawn with a pipette. The non-fat liquid portion was placed in wells at 100 μL for analysis. The concentration of AFM1 in the milk samples was analyzed by AFM1 test kit.The milk samples with AFM1 levels greater than 50 ng/L were confirmed by using High-Performance Liquid Chromatography (HPLC). An Ochratoxin A Serum / Milk ELISA test kit was used for the analyses of OTA. The analyses were made according to the manufacturer’s instructions, and samples were analyzed in duplicate. The absorbance value of milk samples was obtained from the ELISA plate reader at 450 nm. The mean value of AFM1 was found to be 19.54 ng/L in the milk samples. According to the European Commission (EC), the maximum limit for AFM1 in milk is 50 ng/L. In our study, eight (7.61%) of the 105 samples exceeded this limit. The mean value of OTA was found to be 119 ng/L in the milk samples. The relationship between milk type and levels of AFM1 was found to be significant at (P < 0.01). The mean value of AFM1 in pasteurized milk was found statistically significant and lower than raw milk (P < 0.05). The difference between levels of OTA and milk type was not statistically significant at (P > 0.05). Discussion: Milk is a great protein source especially for children in the age of growth. Yeasts such as Fusarium, Aspergillus and Penicillium produce mycotoxins that cause food, feed contamination. Owing to carcinogenic, mutagenic and teratogenic effects of AFM1, presence of AFM1 in milk samples may adversely affect human health. The presence of AFM1 in different contamination levels can be observed in milk and milk products. Factors such as ration type, climate conditions, feed storage conditions, feeding regime and health status of dairy animals may be effective in the occurrence of these contamination. It is necessary to establish legal limits by conducting effective research on the existence of OTA in animal-derived products. The existence of mycotoxins in milk and dairy products can be reduced by preventing the contamination of feed materials with yeast and molds used in the feeding of dairy cows. Milk is one of the most important protein source for the human, effective hygienic controls should be applied to prevent microbiological and chemical hazards. Our data suggest that heat-treated milk may also be dangerous to human health, mycotoxins contamination should be controled with monitoring programs routinely in milk and feed materials for food safety. Determination of Aflatoxin M1 and Ochratoxin A in Raw, Pasteurized and UHT Milk in Turkey